Diapause affects cuticular hydrocarbon composition and mating behavior of both sexes in Drosophila montana. (3rd October 2018) - Ala‐Honkola, Outi; Kauranen, Hannele; Tyukmaeva, Venera; Boetzl, Fabian A.; Hoikkala, Anneli; Schmitt, Thomas
Abstract: Environmental cues, mainly photoperiod and temperature, are known to control female adult reproductive diapause in several insect species. Diapause enhances female survival during adverse conditions and postpones progeny production to the favorable season. Male diapause (a reversible inability to inseminate receptive females) has been studied much less than female diapause. However, if the males maximized their chances to fertilize females while minimizing their energy expenditure, they would be expected to be in diapause at the same time as females. We investigated Drosophila montana male mating behavior under short‐day conditions that induce diapause in females and found the males to be reproductively inactive. We also found that males reared under long‐day conditions (reproducing individuals) court reproducing postdiapause females, but not diapausing ones. The diapausing flies of both sexes had more long‐chain and less short‐chain hydrocarbons on their cuticle than the reproducing ones, which presumably increase their survival under stressful conditions, but at the same time decrease their attractiveness. Our study shows that the mating behavior of females and males is well coordinated during and after overwintering and it also gives support to the dual role of insect cuticular hydrocarbons in adaptation and mate choice.